Provincial Economies and Electricity Consumption in Thailand: เศรษฐกิจจังหวัดและการใช้ไฟฟ้าในประเทศไทย - Pattamasiriwat, Direk; Stargell, Pawinee; Inon, Meradee (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ บทความกำหนดวัตถุประสงค์ 2 ประการ 1) เพื่อศึกษาความสัมพันธ์ระหว่างเศรษฐกิจจังหวัดและความต้องการใช้ไฟฟ้า 2) เพื่อเปรียบเทียบความเข้มข้นของการใช้ไฟฟ้าระหว่างจังหวัด (Provincial Electricity Intensity) ต่อ GPP โดยสันนิษฐานว่า ความต้องการใช้ไฟฟ้ามีแนวโน้มขยายตัวตามมูลค่าการผลิตของแต่ละจังหวัด สะท้อนในค่าความยืดหยุ่น (Demand Elasticity for Electricity to GPP) พร้อมตั้งข้อสันนิษฐานว่าความเข้มข้นของการใช้พลังงานไฟฟ้าในแต่ละจังหวัดมีความแตกต่างกัน ทำการวิเคราะห์โดยใช้แบบจำลองทางเศรษฐมิติที่ประมาณด้วยวิธีกำลังสองน้อยที่สุดสองชั้นผ่านตัวแปรเครื่องมือโดย ใช้ข้อมูลรายจังหวัดในช่วงเวลา พ.ศ. 2551-2560 ผลการศึกษาพบว่า (1) อัตราการขยายตัวของความต้องการใช้ไฟฟ้า ร้อยละ 4.8 ใกล้เคียงกับอัตราการขยายตัวของ GPP (2) ความเข้มข้นของการใช้ไฟฟ้าระหว่างจังหวัดแตกต่างกันอย่างมีสำคัญ คือจังหวัดที่อิงฐานอุตสาหกรรม มีความต้องการไฟฟ้าเข้มข้นกว่าจังหวัดที่อิงฐานการเกษตรและการบริการ (3) การวัด ค่าความยืดหยุ่นต่อ GPP จำแนกในกลุ่มผู้ใช้ ในภาคครัวเรือนค่าความยืดหยุ่นประมาณ 0.63 ในกลุ่มผู้ประกอบการขนาดย่อม ค่าความยืดหยุ่น 0.77 และในกลุ่มผู้ประกอบการขนาดกลาง ค่าความยืดหยุ่น 0.72 และในผู้ประกอบการขนาดใหญ่ ค่าความยืดหยุ่นสูงกว่า 0.94 กำหนดให้ปัจจัยอื่นๆ คงที่ ค่าความยืดหยุ่น ที่แตกต่างกันตามกลุ่มผู้ใช้แสดงให้เห็นว่าการเปลี่ยนแปลงเศรษฐกิจจังหวัด หรือ GPP ส่งผลต่อความต้องการใช้ไฟฟ้าของแต่ละกลุ่มผู้ใช้ไม่เท่ากันขึ้นกับกลุ่มผู้ใช้ไฟฟ้า ABSTRACT This paper aims to set for two modest objectives: First, to empirically explore the relationship between provincial economies and electricity consumption; Secondly, to observe difference in electricity intensity by provinces (measured by electricity consumption per million baht of GPP). It is hypothesized that electricity consumption is positively related to GPP and that there may be variations in the demand elasticity by provinces. The relationship as assumed in the mode is estimated by the two-stage least squares with instrumental variable (IV-2SLS) regression. The unit of analysis in this case refers to 77 provinces over 10-year span (BE2551-2560). Among our findings: (1) the growth of electricity consumption averaged to 4.8 percent per annum which is approximately equal to that of GPP, (2) difference in electricity intensity among provinces is confirmed with the note that the industrial based provinces tend to be intensive use of electricity in relation to those provinces which are agriculture-based or service-based, and (3) the demand elasticity for different types of user are reported: namely, 0.63 for residential consumption, 0.77 for small enterprises, 0.72 for medium enterprises, and 0.94 for large enterprises.